2015
DOI: 10.1002/path.4504
|View full text |Cite
|
Sign up to set email alerts
|

DMP1β, a splice isoform of the tumour suppressor DMP1 locus, induces proliferation and progression of breast cancer

Abstract: Our recent work has indicated that the DMP1 locus on 7q21, encoding a haplo-insufficient tumour suppressor, is hemizygously deleted at a high frequency in breast cancer. The locus encodes DMP1α protein, an activator of the p53 pathway leading to cell cycle arrest and senescence, and two other functionally undefined isoforms, DMP1β and DMP1γ. In this study, we show that the DMP1 locus is alternatively spliced in ∼30% of breast cancer cases with relatively decreased DMP1α and increased DMP1β expression. RNA-seq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 39 publications
3
87
0
Order By: Relevance
“…Recent researches have demonstrated positive roles of aberrant splicing in carcinogenesis (6371). The full-length Ets1 (p51-Ets1) and Ets1 ΔVII (p42-Ets1) isoforms (57) have key distinctions regarding protein-protein interactions, DNA-binding kinetics, and transcriptional target specificity (72).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…Recent researches have demonstrated positive roles of aberrant splicing in carcinogenesis (6371). The full-length Ets1 (p51-Ets1) and Ets1 ΔVII (p42-Ets1) isoforms (57) have key distinctions regarding protein-protein interactions, DNA-binding kinetics, and transcriptional target specificity (72).…”
Section: Ets1 and Ets2mentioning
confidence: 99%
“…The human DMP1 ( DMTF1 ) locus encodes two other splice variants, DMP1β and DMP1γ. We recently reported that DMP1β accelerates G1-S progression and contributes mammary carcinogenesis in vivo (51). On the other hand, the biology of DMP1γ in cell proliferation, apoptosis, and/or tumorigenesis is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that DMP1β does not bind to p53 (data not shown); whether or not DMP1γ binds to p53 has not been studied. It is very likely that they DMP1γ does not affect the function of p53 because i) it lacks the 2 nd and 3 rd Myb-like domain required for the physical interaction with p53 (52), and ii) DMP1β accelerated the proliferation breast cancer cells independent of p53 (51). To date 40 splice variants have been reported from the hDMP1 locus (89), but only two of them -aAug10 (hDMP1α) and bAUG10 (a variant that lacks the amino-terminal 88 amino acids) encode proteins that can bind to p53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations